Pharmacodynamic analysis of eribulin safety in breast cancer patients using real‐world postmarketing surveillance data. Issue 9 (23rd July 2018) - Kawamura, Takahisa; Kasai, Hidefumi; Fermanelli, Valentina; Takahashi, Toshiaki; Sakata, Yukinori; Matsuoka, Toshiyuki; Ishii, Mika; Tanigawara, Yusuke
Abstract : Postmarketing surveillance is useful to collect safety data in real‐world clinical settings. In this study, we applied postmarketing real‐world data on a mechanistic model analysis for neutropenic profiles of eribulin in patients with recurrent or metastatic breast cancer. Demographic and safety data were collected using an active surveillance method from eribulin‐treated recurrent or metastatic breast cancer patients. Changes in neutrophil counts over time were analyzed using a mechanistic pharmacodynamic model. Pathophysiological factors that might affect the severity of neutropenia were investigated, and neutropenic patterns were simulated for different treatment schedules. Clinical and laboratory data were collected from 401 patients (5199 neutrophil count measurements) who had not received granulocyte colony‐stimulating factor and were eligible for pharmacodynamic analysis. The estimated mean parameters were as follows: mean transit time = 104.5 h, neutrophil proliferation rate constant = 0.0377 h −1, neutrophil elimination rate constant = 0.0295 h −1, and linear coefficient of drug effect = 0.0413 mL/ng. Low serum albumin levels and low baseline neutrophil counts were associated with severe neutropenia. The probability of grade ≥3 neutropenia was predicted to be 69%, 27%, and 27% for patients on standard, biweekly, and triweekly treatment scenarios, respectively, based on virtual simulations using the developed pharmacodynamic model. In conclusion, this is the first application of postmarketing surveillance data to a model‐based safety analysis. This analysis of safety data reflecting authentic clinical settings will provide useful information on the safe use and potential risk factors of eribulin. Abstract : This article reports the first application of postmarketing real‐world data on a mechanistic pharmacodynamic model for neutropenic profiles by eribulin. Low serum albumin and low baseline neutrophil counts were associated with severe neutropenia. The probability of grade ≥3 neutropenia was predicted in different dosing schedules, based on virtual simulations using the developed pharmacodynamic model.